PEMANFAATAN SEKAM PADI SEBAGAI BRIKET BIOMASSA UNTUK ENERGI ALTERNATIF - Ronting, Friska Valencia (Universitas Mulawarman, 2026)
The increasing demand for energy along with the depletion of fossil fuel resources encourages the development of renewable and environmentally friendly alternative energy sources. Indonesia, as an agricultural country, produces a large amount of rice husk waste which has not been optimally utilized. This study aims to evaluate the potential of rice husk as biomass briquettes for alternative energy. The research method includes rice husk carbonization, briquette molding using clay as a binder, and characterization tests such as calorific value, moisture content, ash content, combustion rate, and combustion performance. The results indicate that rice husk briquettes have adequate calorific value, stable combustion characteristics, and potential application as renewable energy sources. This study concludes that rice husk biomass briquettes can be developed as an alternative fuel to reduce dependence on fossil energy and improve agricultural waste utilization.